2017
DOI: 10.1017/ice.2017.73
|View full text |Cite
|
Sign up to set email alerts
|

Management of Risks From Water and Ice From Ice Machines for the Very Immunocompromised Host: A Process Improvement Project Prompted by an Outbreak of Rapidly Growing Mycobacteria on a Pediatric Hematopoietic Stem Cell Transplant (Hsct) Unit

Abstract: BACKGROUND In 2011, pediatric hematopoietic stem cell transplant (HSCT) patients were moved from an older hospital to a new children's hospital. To minimize bacterial growth in the new hospital's water during construction, the plumbing system was flushed and disinfected before occupancy. However, 6 months after occupancy, an increased incidence of rapidly growing mycobacteria (RGM) was detected in clinical cultures. Over 10 months, 15 pediatric HSCT patients were infected, while no pediatric HSCT patients had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The female patient case was related to a positive cold-water sample from a tap in the patient room. Third, infection preventionists and healthcare leadership teams were baffled to be investigating a waterborne pathogen issue in a newly constructed area or building [17,22,24,39]. Baker et al [17] reported this type of incident in a two-phase outbreak involving Mycobacterium abscessus.…”
Section: Gap #3: Establish Water Management For Construction and Commismentioning
confidence: 99%
See 3 more Smart Citations
“…The female patient case was related to a positive cold-water sample from a tap in the patient room. Third, infection preventionists and healthcare leadership teams were baffled to be investigating a waterborne pathogen issue in a newly constructed area or building [17,22,24,39]. Baker et al [17] reported this type of incident in a two-phase outbreak involving Mycobacterium abscessus.…”
Section: Gap #3: Establish Water Management For Construction and Commismentioning
confidence: 99%
“…Other opportunistic waterborne pathogens such as NTM and Sphingomonas, spp. accounted for 197 (22%) disease cases and 29 (26%) deaths [17,24,33]. Investigators conducting studies about non-Legionella waterborne pathogens find minimal emphasis is placed on water management across all microbials (i.e., all genera/species) [24,27,55].…”
Section: Gap #4: Moving Beyond Legionellamentioning
confidence: 99%
See 2 more Smart Citations
“…The cause of this outbreak was determined to be high heterotrophic plate counts (bacterial colony forming units/ml water), including rapidly growing mycobacteria, in the water and ice from the drinking water and ice machines on the pediatric BMT unit. Ultimately, the high heterotrophic plate counts in drinking water and ice were reduced by several different interventions, including 0.005-μm filters for the water entering the drinking water and ice machines, silver-impregnated components in the machines and copper tubing for pipes leading to the drinking water and ice machines, and the addition of UV disinfection devices to the machines [25••, 35]. …”
Section: Epidemiologymentioning
confidence: 99%